Influence of parental involvement and peer support on mathematics engagement among Malaysian secondary school students - Mohd Din, Norakusuma; Mohd Ayub, Ahmad Fauzi; Ahmad Tarmizi, Rohani (Institute for Mathematical Research, Universiti Putra Malaysia, 2016)
The aim of this study is to explore these two factors that contribute to shifts in student mathematics engagement among secondary boarding school students. The investigation involved a correlational study of 313 respondents were chosen using proportionate stratified sampling from 13 different secondary boarding schools in Malaysia. The findings of this study revealed students were engaged in mathematics with an overall mean of 3.76 (SD = .36) on a likert scale of 1 - 5. They were more engaged in behavior (M = 3.88, SD = .480) than affective (M = 3.80; SD= .460) or cognitive (M = 3.61, SD = .430) domains. It was also found students received good support from peers (M=4.05, SD= 0.530) and parents (M=3.47, SD= .680). Correlational analysis also showed positive relationships between parents’ involvement (r = .480; p < .001), peer support (r = .490; p < .001) and students’ mathematics engagement. Further analysis indicated these two factors influenced students’ mathematic engagement in the classroom. This study provide evidence on the importance of peer support and parental involvement to increase students’ mathematics engagement in the classroom.